Decision making factors in vegetable crop selection by farm enterpreneurs in Benguet province - Tagarino, Darlyn Damasco (Animo Repository, 1994)
Farm entrepreneurs engaged in vegetable crops production in Atok and Buguias, Benguet, Philippines are assessed of crop choice decisions.The focus was on identifying the crucial crop selection variables by a variety of approaches. The basic methodology was a survey of 120 farm entrepreneurs identified via a three-stage random sampling.The first approach identifies the crop choice variables using own-farm entrepreneur's priority ranking. The 5 top-most variables identified were climate, pests and diseases, capital, irrigation and market price. The second approach factor analyzes a set of 27 hypothesized crop choice variables to reduce them into a smaller set of components. Eight factors were found to best summarize the underlying relationships between these variables: viability, availability, expectancy, certainty, marketability, manageability, profitability and dimensionality.In identifying the process of crop choice variables, the personal and farm profile of the farm entrepreneurs were described. Eighty-five percent were males, 55 percent had reached or finished the elementary level mean age was 40.2 and modal household size was 6. On the other hand, mean farm size was 4,646 sq.m., 64 percent were one-crop farms, 73 percent were irrigated, and 81 percent were owner-operated. Crop choice decision making was described in areas of planting objectives, current crop choices, choice variables considered, and follow-up and control measures. This was for the farm entrepreneurs in general and by specific groups (i.e., between single crop growers, between crop mix growers and between single crop and crop mix growers). Foremost objectives in planting and in rank order were to maximize returns, maintain consumption, and maintain status quo. The crops planted were potato (73 percent), cabbage (27), chinese cabbage (13), carrots (17), sweet peas (5), lettuce (8) and radish (1). The most popular follow-up and control measure was to scout and sell to crop buyers offering the highest price. The univariate chi square test showed that significant differences exist among farm entrepreneurs given some crop choices and some crop choice variables by farm size and by farm location. The Two-Way Analysis of Variance showed a significant difference among farm entrepreneurs according to ranked crop choice variables. Multivariate Discriminant Analysis was explored to identify variables that discriminate a crop producer from other crops producers.The study revealed that actual vegetable crop choices are limited to a few that crop array, farm size and farm location generally influence crop choices and identification of choice variables that crop choice decision making is differentiated by crop groups and that crop choice decision variables are multi-dimensional than unitary.